2017
DOI: 10.21925/mplsheartjournal-d-17-00012
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Implantable Cardiac Monitors: A Comparison of Reveal XT and LINQ Patient Selection, Arrhythmia Detection, and Clinical Outcomes

Abstract: Implantable cardiac monitors (ICMs) are useful for long-term arrhythmia monitoring in patients with unexplained symptoms. Temporal trends in the use of ICMs in routine clinical practice, along with the clinical indications for use, arrhythmia detection accuracy, and association with clinical outcomes have not been described. We identified all patients who underwent ICM implantation at the Minneapolis Heart Institutet between January 1, 2011, and February 26, 2016, using diagnosis codes for device implantation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Clinical expert opinion and evidence from a mixed population suggest that the Reveal LINQ has better specificity than the XT (see Chapter 3), is easier to implant and leads to fewer complications due to its size, and that AF detection accuracy between the devices is similar. 28 Medtronic highlighted that the size of Reveal LINQ differentiates it from other devices and means that a smaller incision in the skin is required (< 1 cm). Clinical experts at the NICE scoping workshop reported that the procedure can be done by health-care professionals other than cardiologists (e.g.…”
Section: Reveal Linqmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical expert opinion and evidence from a mixed population suggest that the Reveal LINQ has better specificity than the XT (see Chapter 3), is easier to implant and leads to fewer complications due to its size, and that AF detection accuracy between the devices is similar. 28 Medtronic highlighted that the size of Reveal LINQ differentiates it from other devices and means that a smaller incision in the skin is required (< 1 cm). Clinical experts at the NICE scoping workshop reported that the procedure can be done by health-care professionals other than cardiologists (e.g.…”
Section: Reveal Linqmentioning
confidence: 99%
“…Clinical expert opinion and evidence from a mixed population suggest that the Reveal LINQ may have better sensitivity and specificity for detecting AF than the Reveal XT and is likely to lead to fewer complications owing to its size, but there are no head-to-head clinical trials to confirm these findings in a CS population. 28 In addition, no clinical or DTA data suitable for inclusion were identified for the BioMonitor 2-AF or Confirm Rx devices, despite widening the eligibility criteria to include low-quality non-comparative observational studies. Data for the BioMonitor 2-AF or Confirm Rx devices were limited to mixed population diagnostic accuracy and single-arm observational studies submitted by the companies.…”
Section: Clinicalmentioning
confidence: 99%